1995
DOI: 10.1093/oxfordjournals.humrep.a135994
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Clinical value of sperm morphology for in-vivo fertility: comparison between World Health Organization criteria of 1987 and 1992

Abstract: The World Health Organization (WHO, 1992) has suggested new criteria for scoring sperm morphology. This study compares the clinical value of the new criteria, i.e. classification of a man as fertile or infertile, to those previously established by the WHO (1987). Papanicolaou-stained semen smears from 166 men attending our infertility clinic, whose fertility status was known, were scored using both methods. Using logistic discriminant analysis for compositional data, no difference between these two sets of cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…Several authors found these values to be of little or no clinical value [7,9,10] . These articles did, however, fi nd a positive correlation between the high proportion of morphologically normal sperms and the increased likelihood of fertility and/or pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors found these values to be of little or no clinical value [7,9,10] . These articles did, however, fi nd a positive correlation between the high proportion of morphologically normal sperms and the increased likelihood of fertility and/or pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a positive correlation between normal semen parameters and male fertility potential, the threshold values for fertility/subfertility according to WHO criteria [1,2] are of little clinical value in discriminating between the fertile and the subfertile male [7][8][9][10][11] . If these criteria were applied, a great number of fertile males (partners having had pregnancies shortly before, after, or at the time of a spermiogram) were classifi ed as subfertile.…”
mentioning
confidence: 99%
“…De plus, en r~ponse ~i I'~tude de Ducot et al [21], I'IAM devient le TZP (index de t6ratozo-ospermie) qui est la moyenne du nombre d'anomalies par spermatozo'ide anormal [33]. Barratt et al [3] ont compare la signification clinique de la morphologie des spermatozoides evalu~s par les crit6res de I'OMS de 1987 et de 1992. IIs ont conclu que I'~dition de 1992 n'apportait pas de changement majeur dans la valeur predictive de ce param~tre pour d6terminer la fertilit6 du patient.…”
Section: C) Classification De Romsunclassified
“…Although these criteria have been updated three times, many investigators still considered some of the values, such as the percentage of normal morphology, inappropriate [8][9][10] . A cutoff point of 30% on normal morphology was considered overly strict and 10-20% appeared to be more appropriate [8,11,12] .…”
Section: Introductionmentioning
confidence: 99%